STRATEGI PENGEMBANGAN AGROWISATA KOLAM PANCING P4S KARYA AGRI DI KELURAN BATUPLAT KECAMATAN ALAK KOTA KUPANG - Muhammad Rizky Zola; Sondang S. P. Pudjiastuti; Santhy Chamdra (Buletin Ilmiah Impas, 2023)
This study aims to determine 1.) the driving and inhibiting factors for the development of P4S Karya Agri fishing pound agrotourism, 2.) Karya Agri P4S fishing pond agrotourism development strategy. The method used in this study is a descriptive analysis method. The respondents in this study are the owners of the P4S Karya Agri fish ponds, the fish pond workers, the fish pond visitors from a total of 85 people obtained with the Slovin approach formula, the head of the departement of tourism destinasions of the Kupang City Tourism Bureau, the Head of the Tourism Destinasions Departement of the Kupang City Tourism Bureau, the area cultivation of the Kupang City Fisheries Service. Data analysis tools used in this study 1.) IFAS and EFAS analysis 2.) SWOT analysis. This research is qualitative, the results show that 1.) the driving factors for the development from within (strengths), wich receive the highest category, are beautiful, cool and untouched natural panorama with an average of 3.76, inhibiting factors for the development from within (weaknesses) the highest category is given to the tourism development program, which is still simple 1.64, the driving factor for external development (opportunity) the highest category is a given to the area that offers the flexibility to develop tourism potential 3.68, the inhibiting factor for development of outside (threats) which received the highest category, was the 1.45 implementation of restrictions on community activities. 2.) Karya Agri P4S fishing pond agrotourism development strategy based on SWOT analysis is an SO strategy, as the cut – off point in quadrant (2.23 : 1.68) is in a growth position that has the strengths should make optimal use of it and it has possibilities.